Insecticidal Activity, Kinetics and Mechanism of Hydrolysis of Bis-3-nitro-p-touidine phosphate via Conjugate Acid Species - Patil, R.; Shinde, C.P.; Kulshrestha, N. (Asian Journal of Chemistry, 2010)
Bis-3-nitro-p-toluidine phosphate was found to be a good insecticide. Kinetic study has been investigated in acid region from 0.1 to 6.0 mol dm–3 at 98ºC in 30% dioxane-water mixture (v/v). Ionic strength data exhibits the participation of conjugate and neutral species. Bimolecular behaviour has been decided by molecularity data studies. Solvent isotope effect study favours specific acid catalysis. The formation of a transsition state has been observed by solvent effect study. Phosphorus-nitrogen bond fission has been further strengthened by isokinetic relationship.